2017
DOI: 10.1111/ele.12794
|View full text |Cite
|
Sign up to set email alerts
|

Less favourable climates constrain demographic strategies in plants

Abstract: Correlative species distribution models are based on the observed relationship between species’ occurrence and macroclimate or other environmental variables. In climates predicted less favourable populations are expected to decline, and in favourable climates they are expected to persist. However, little comparative empirical support exists for a relationship between predicted climate suitability and population performance. We found that the performance of 93 populations of 34 plant species worldwide – as meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 49 publications
8
99
1
Order By: Relevance
“…Our analyses show that mismatches between species’ distributions and density or demographic rates along the SWB gradient are common, but highly variable among species. These results extend a growing body of research, suggesting that patterns in occurrence do not necessarily match current patterns in density and demographic rates (Diez et al ; Thuiller et al ; Csergő et al ; Pironon et al ). Because current densities of long‐lived species are determined by past demographic performance, any factors that lead to changes in performance over time may lead to mismatches between current performance and distributions.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our analyses show that mismatches between species’ distributions and density or demographic rates along the SWB gradient are common, but highly variable among species. These results extend a growing body of research, suggesting that patterns in occurrence do not necessarily match current patterns in density and demographic rates (Diez et al ; Thuiller et al ; Csergő et al ; Pironon et al ). Because current densities of long‐lived species are determined by past demographic performance, any factors that lead to changes in performance over time may lead to mismatches between current performance and distributions.…”
Section: Discussionsupporting
confidence: 72%
“…Although there is again mixed evidence among species and studies, recruitment patterns are generally not well matched to adult distributions, and the differences do not tend to suggest directional migration in response to changing climate (Zhu et al ; Serra‐Diaz et al ; Wason & Dovciak ). Studies comparing distributions to predicted population growth rates have also shown significant mismatches between where species are present and where they are predicted to perform well (Diez et al ; Merow et al ; Csergő et al ). Overall, these studies offer significant evidence that species are not always distributed where they perform best, but the mechanisms and generality of these relationships remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…A3), the smaller the set of species the higher the probability the hypothesis is supported by chance. Similarly, studies focusing on environmental suitability and demographic rates in plants found contrasting results (Thuiller et al 2014, Pironon et al 2015, Csergő et al 2017. Here we estimated geographic and niche measures on the entire geographic range of the species, therefore presumably better capturing the centrality/marginality patterns.…”
Section: Discussionmentioning
confidence: 98%
“…These trimmed models were generated through a pixel‐by‐pixel analysis to prevent large overlaps between species’ distributions. First, we rescaled the predicted suitability values (from the ENMs analysis) within untrimmed models to range between 0 and 1, in order to make predictions comparable across species (Csergő et al, ). Then, within the overlapping area of a species pair, the species with the higher (rescaled) suitability score was considered as present in the pixel at the expense of the other.…”
Section: Methodsmentioning
confidence: 99%